Inequalities for the Polar Derivatives of a Polynomial (Analysis in Theory and Applications, 2014)
Let $P(z)$ be a polynomial of degree $n,$ having all its zeros in $|z|≤ 1.$ In this paper, we estimate $kth$ polar derivative of $P(z)$ on $|z|=1$ and thereby obtain compact generalizations of some known results which among other things yields a refinement of a result due to Paul Turán.